Endothelin A receptor blockade improves endothelium-dependent relaxation in obese woman - Gradin, K; Persson, B (Physiological research, 2018)
Hypertension in obesity is associated with increased insulin resistance, vascular mass and body mass index (BMI). The purpose of the study was to visualize endothelin-1 (ET-1) mediated constriction in arteries isolated from subcutaneous adipose tissue from obese hypertensive women previously operated by gastric bypass. Functional studies were conducted in a microvascular myograph. Expressed as percentage of contraction elicited by 124 mM KCl concentration-response curves for ET-1 were shifted leftward in arteries from obese hypertensive patients compared to healthy normotensive subjects. The vasodilator response to the ET-1 antagonist BQ123 (1 microM) was significantly higher in arteries from obese hypertensive patients (p<0.001). BQ123 induced relaxation was inhibited by NO synthase inhibitor L-NAME (0.1 nM). Preincubation with BQ123 enhanced the relaxation induced by acetylcholine (ACh; 0.1 nM - 0.1 mM) (p<0.001), but not that induced by NO donor sodium nitroprusside (SNP; 0.1 nM - 0.1 mM), in arteries from obese hypertensive patients. The present study show that hypertension yet prevail after gastric bypass surgery and the ET(A) receptor antagonist BQ123 may be a useful tool in reducing blood pressure in obese hypertensive patients.
Keywords: antagonisté endotelinového receptoru A; vazodilatace; hypertenze; orgánové kultury - kultivační techniky; Obesity; cévní endotel; tuková tkáň; receptor endotelinu A; vztah mezi dávkou a účinkem léčiva; obezita; Endothelium, Vascular; Organ Culture Techniques; Hypertension; Vasodilation; Endothelin A Receptor Antagonists; Receptor, Endothelin A; žaludeční bypass; lidé; Adipose Tissue; ženské pohlaví; Peptides, Cyclic; Humans; Gastric Bypass; cyklické peptidy; Female; Dose-Response Relationship, Drug; lidé středního věku; Middle Aged